How to Teach Science for Elementary Gifted Students. a Case Study Done at Cgs Cianjur in Indonesia - Surachman Dimyati; Asnah Said (Bandar Lampung University (UBL), 2014)
Science should be taught in certain ways in order to lead and encourage students to get the optimum results in education. The use of the inquiry method in teaching science, especially for gifted students is more sound than other strategies. Some researchers, on the matter of inquiry showed that only advanced learners shown how to construct new knowledge from the text. Other scholars argued that teachers whose pedagogical approach promoted inquiry were more successful than those who implemented a direct teaching approach. Others issues regarding science and studies related will be discussed.Students’ characteristics, variety of teaching methods for teachers, understanding the role of the gifted students’ parents, and also the schools support better results for the gifted students are also discussed scholarly and other field observation and interviews with the administrations, teachers, parents, and students done in Cugenang Gifted School, Cianjur, West Java.